Combining Radon Deficit, NAPL Concentration, and Groundwater Table Dynamics to Assess Soil and Groundwater Contamination by NAPLs and Related Attenuation Processes - Martina Mattia; Paola Tuccimei; Giancarlo Ciotoli; Michele Soligo; Claudio Carusi; Elisa Rainaldi; Mario Voltaggio (Applied Sciences, 2023)
Soil and groundwater contamination by NAPLs (Non-Aqueous Phase Liquids) is certainly a big issue for protecting the environment. In situ clean-up actions are routinely applied to mitigate the risk and are supplemented by monitoring surveys to assess the degree, extension, and evolution of the contamination. Radon gas is here used as a tracer of contamination because of its high solubility in non-polar solvents that produce a reduced concentration of the gas in polluted soil and groundwater with reference to radon levels in adjacent “clean” areas. This approach was employed in two sites where gasoline and diesel spillage occurred, causing soil and groundwater contamination. The two case studies were chosen because of their difference in terms of the hydrogeological features, age of the spillage, composition of residual NAPLs, and clean-up measures to test the advantages and limits of this approach in a variety of settings. Radon data, NAPL concentration in the groundwater (mainly total hydrocarbons, Methyl Tertiary-Butyl Ether and Ethyl Tertiary-Butyl Ether) and the depth of the groundwater table were periodically collected in surveys that spanned a period of two years. This dataset was statistically processed using principal component analysis to unravel which factors and attenuation processes are working in the sites and the response of the radon deficit approach to this complex series of phenomena concurrently occurring there.